Investigate the efficiency and effectiveness of material handling in a pharmaceutical factory - Cen, Yizhe (2014)
The sustainability and effectiveness of material handling was looked into in a pharmaceutical factory to support the rapidly growing production demand. An analytical problem analysis was done to understand the number, variability and growth of movements in order to forecast the utilization of current material handling capacity. This was followed by simulation-based analysis to verify and identify the real problem driver. The current material handling was predicted unable to handle the movement demand beyond year 2013. The space adjustment time spent by the forklift trucks was identified as the bottleneck to the problem. Three solutions—charging in the warehouse, conveyor and additional forklift truck were proposed to sustain the material handling capacity beyond 2016. Simulation-based analysis and financial analysis were performed to prove that the additional forklift truck solution was more cost-effective in the short run and the conveyor solution was better suited in the long run.